Embodied Dzikir: Pengalaman Spiritual Penari Whirling dalam Tarekat Naqsabandiyah Haqqani Rabbani di Indonesia - Ridwan, Ahmad; Sururin,; Zamhari, Arif (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
This study aims to describe the practice of whirling dance within the Naqshbandiyya Haqqani Rabbani Order in Indonesia, explore the underlying understanding of its practitioners, and uncover the spiritual experiences associated with this ritual. The central focus is to examine the role of whirling as a form of dynamic dhikr and spiritual transformation within the context of contemporary Sufi practices. This research employs a qualitative approach with a phenomenological method. Data were collected through participant observation and in-depth interviews with whirling dancers affiliated with the Naqshbandiyya Haqqani Rabbani community. The analysis focused on the dancers' subjective experiences and spiritual reflections during the practice. The findings reveal three main points. First, the whirling dance in the Naqshbandiyya Haqqani context is not merely an artistic expression but a structured, symbolic ritual of dhikr, representing the cosmic movement toward unity with the Divine. Second, the dancers possess a deep Sufi understanding of the dance, interpreting it as a manifestation of fana (self-annihilation) and ego transcendence. Third, the spiritual experience during whirling touches on core elements of Sufi psychology—qalb (heart), nafs (soul), and ruh (spirit)—resulting in observable changes in behavior, inner tranquility, and enhanced daily dhikr quality. Theoretically, these findings contribute to the discourse of contemporary Sufism, particularly concerning the role of embodied expressions in dhikr rituals and the relevance of embodied spirituality approaches in the study of Islamic mysticism. The whirling dance exemplifies the integration of bodily movement and spiritual consciousness along the Sufi path.